Re‐evaluation of certain aspects of the EFSA Scientific Opinion of April 2010 on risk assessment of parasites in fishery products, based on new scientific data. Part 2 - Allende, Ana; Alvarez‐Ordóñez, Avelino; Bortolaia, Valeria; Bover‐Cid, Sara; De Cesare, Alessandra; Dohmen, Wietske; Guillier, Laurent; Herman, Lieve; Jacxsens, Liesbeth; Nauta, Maarten; Mughini‐Gras, Lapo; Ottoson, Jakob; et al. (EFSA journal, 2024)
The objective of this opinion was to determine if any wild caught fish species, originating from specific fishing grounds and consumed in the EU/EFTA could be considered free of zoonotic parasites. In this Opinion the term ‘fishery products’ only refers to fresh finfish. As there are multiple fish species and numerous potential parasites, Anisakis sp. was used as an indicator of zoonotic parasites in marine areas. This parasite species is particularly suited as it is common in marine environments, capable of infecting multiple fish species and is the subject of the majority of published studies. On the rare occasion where Anisakis sp. data were not available, or all tests were negative, other parasites such as Contracaecum osculatum (s.l.) and/or Phocanema spp. were considered. In freshwater systems, all zoonotic parasites were investigated. Consumption, import and landing data were used to determine the most relevant fish species and, where possible, the source fishing areas were identified. The most commonly consumed wild caught fish species in the EU/EFTA include tuna, cod, Alaskan pollock, hake, herring, sardines, mackerel, trout and saithe. Although the majority of these fish are caught in the Atlantic Ocean, the Mediterranean and the Black Sea (37) as well as several areas in the Indian Ocean, imported fish may originate from any global fishing areas, with the exception of Antarctica. Based on the data, at least one zoonotic parasite has been reported in at least one fish species in each of the FAO marine fishing areas. Thus, due to relative low fish host specificity of the zoonotic parasites, the panel concluded that all wild caught fish species may be exposed to and infected with zoonotic parasites. The same applies to freshwater fishing areas, with many areas having multiple studies reporting the presence of zoonotic parasites in the wild caught fish species.